2004
DOI: 10.1115/1.1756589
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Flow and Heat Transfer in Rectangular Micro-Channels

Abstract: Knowledge of flow pattern and flow pattern transitions is essential to the development of reliable predictive tools for pressure drop and heat transfer in two-phase micro-channel heat sinks. In the present study, experiments were conducted with adiabatic nitrogen-water two-phase flow in a rectangular micro-channel having a 0.406×2.032mm2 cross-section. Superficial velocities of nitrogen and water ranged from 0.08 to 81.92 m/s and 0.04 to 10.24 m/s, respectively. Flow patterns were first identified using high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Additionally, most investigators conclude that, while macrochannel flow regime maps do capture overall qualitative trends, they cannot be relied upon for quantitative predictions. Figure 16(a) shows a flow module that was constructed by Qu et al [115] to investigate adiabatic two-phase flow regimes in a horizontal 0.406 mm deep, 2.032 mm wide, and 12 cm long microchannel. Figure 16(b) depicts the construction of a mixer containing a 40 lm porous tube, which was used to bubble nitrogen gas from the core into a water stream passing through the annulus between the porous tube and housing.…”
Section: How Useful Are Microchannel Two-phase Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, most investigators conclude that, while macrochannel flow regime maps do capture overall qualitative trends, they cannot be relied upon for quantitative predictions. Figure 16(a) shows a flow module that was constructed by Qu et al [115] to investigate adiabatic two-phase flow regimes in a horizontal 0.406 mm deep, 2.032 mm wide, and 12 cm long microchannel. Figure 16(b) depicts the construction of a mixer containing a 40 lm porous tube, which was used to bubble nitrogen gas from the core into a water stream passing through the annulus between the porous tube and housing.…”
Section: How Useful Are Microchannel Two-phase Flowmentioning
confidence: 99%
“…This also requires the use of proper dimensionless groups in the transition models. As indicate by Qu et al [115], those should include at a minimum Phase Reynolds numbers: Phase Weber numbers:…”
Section: How Useful Are Microchannel Two-phase Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reveals that previous experimental works who tried to identify and differentiate the transition limits between conventional tubes and micro-scale channels, in most cases, disagree in their findings. Some of these studies have concluded that the hydraulic diameter range for microchannels should be between 10 and 200 µm [1,2] while some other studies state that this range should be between 1 and 1000 µm [3][4][5]. Such separation is therefore only conventional, and we will conservatively consider only small channels below 200 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Com o decréscimo do diâmetro hidráulico a partir de uma determinada dimensão constatam-se desvios significativos do comportamento da perda de pressão, transição entre padrões de escoamento e fração de vazio. Qu et al (2004)…”
Section: Transição Entre Micro-e Macro-escalaunclassified